Physiological and biochemical responses of Tanacetum balsamita L. to the foliar application of Dobogen biostimulant, glucose and KNO3 under salinity stress - Mohammad Bagher Hassanpouraghdam; Lamia Vojodi Mehrabani; Mehdi Kheiri; Antonios Chrysargyris; Nikolaos Tzortzakis (Scientific Reports, 2022)
Abstract Salinity is one of the predominant abiotic stress factors that influence the growth and productivity of plants. Salinity adversely impacts the growth responses via ionic toxicity, osmotic stress, impaired nutrients uptake, hormonal disparity, and the over-production of reactive oxygen species. To study the effects of salinity stress (0, 50, 100, and 150 mM) and foliar treatments (dH2O, 2 g L−1 Dobogen biostimulant, 2 g L−1 KNO3, and 2 g L−1 d-glucose) on the growth and physiological responses of Tanacetum balsamita, a factorial experiment was conducted based on the completely randomized design at the research greenhouse of Azarbaijan Shahid Madani University, Iran. The results showed the significant interaction effects of salinity and foliar sprays on chlorophyll a, K+, Na+, Mg2+, Fe2+, Zn2+, Mn2+, and Si content, K/Na ratio, and total phenolics and flavonoids content. The highest phenolic content was acquired with 100 mM salinity and foliar spray of Dobogen and glucose, 50 mM NaCl × KNO3 application, and 50 mM salinity × no-foliar application. The highest K/Na ratio was observed in control plants and controls × KNO3 and/or Dobogen application. The greatest Si content was recorded with no-salinity × Dobogen and KNO3 applications and no-saline × no-foliar (control) plants. The independent effects of treatments influenced malondialdehyde, flavonoids, proline contents, and catalase activity. Chlorophyll b and superoxide dismutase were affected by the salinity. Total soluble solids and Ca2+ content were responsive to the foliar applications. Malondialdehyde and proline content was the highest at 150 mM salinity. Salinity adversely affected the physiological responses of costmary. However, foliar treatments partially ameliorated the salinity effect, and the results with more detailed studies would be advisable to the extension section and pioneer farmers.